SIMBOL PALU DAN EKSISTENSINYA DALAM POLITIK PRAKTIS INDONESIA TAHUN 1955 - Ahmad Randi; Arditya Prayogi (Indra institute Research & Publication, 2022)
In the history of Indonesia, the workers have played a relatively important role in the course of the nation. At a time when the Indonesian people were fighting for independence, the role of the workers could not be ignored, could not be forgotten. They worked hand in hand with other mass groups to free the Indonesian people from the grip of the colonialists. This article aims to reveal how the existence of workers in the socio-political situation and their involvement in practical politics in Indonesia in 1955. This article was written using the historical method which consists of several stages, namely heuristics, criticism, interpretation, and historiography. In this article, it can be concluded that there are political and economic relations between trade unions and various political elements, especially with political parties. The relationship between the two has different interests where labor unions have economic interests in order to get a living wage, health insurance and oppose arbitrary actions by employers. Meanwhile, political parties make themselves as a forum for channeling labor union voice aspirations and use them as a vote base.